Hubungan Kadar Glukosa Darah dengan Kulitas Hidup pada Pasien Diabetes Melitus Tipe II di RSUD Sleman Yogyakarta - Zurdayanis, Zurdayanis; Marfianti, Erlina (JKKI : Jurnal Kedokteran dan Kesehatan Indonesia, 2016)
Diabetes mellitus is a chronic disease with blood glucose levels higher than normal. Prevalence of diabetes mellitus is increasing, especially diabetes mellitus type 2 caused by various factors like lifestyle changed that affect the quality of health care. The quality of health-related quality of life. The aim this study to investigated the relationship between blood glucose level with the quality of life in patients with diabetes mellitus type 2 in Sleman district hospital. The study is descriptive quantitative research with cross sectional analytic. Data taken from questionnaires of quality of life and the medical records patients with diabetes mellitus type 2 in Sleman district hospital, Yogyakarta. Analityc methods to shown association between blood glucose level with the quality of life in patients with diabetes mellitus type 2 used Chi-Square Test. The sample in this study were 64 cases of diabetes mellitus type 2 with inclusion criteria. Diabetes mellitus type 2 with high blood glucose level and lower quality of life as much as 41 cases. For patients diabetes mellitus type 2 with high blood glucose levels and high quality of life for as much as 4 cases. While people with diabetes mellitus type 2 with low blood glucose levels and lower quality of life as much as 5 cases. Patients of diabetes mellitus type 2 with blood glucose levels low and high quality of life as much as 14 cases. There is a significant Association between blood glucose level with the quality of life in patients with diabetes mellitus type 2 (p=0,000). This study concluded that there was a a significant Association between blood glucose level with the quality of life in patients with diabetes mellitus type 2,